The safety of amoxicillin and clavulanic acid use during the first trimester of pregnancy. Issue 12 (3rd December 2019) - Daniel, Sharon; Doron, Maya; Fishman, Boris; Koren, Gideon; Lunenfeld, Eitan; Levy, Amalia
Abstract : Aims: The goal of the current study was to assess the risk for major congenital malformations following first‐trimester exposure to amoxicillin, or amoxicillin and clavulanic acid (ACA). Methods: A population‐based retrospective cohort study was conducted, by linking 4 computerized databases: maternal and infant hospitalization records, drug dispensing database of Clalit Health Services in Israel and data concerning pregnancy terminations. Multivariate negative‐binomial regression was used to assess the risk for major malformations following first‐trimester exposure, adjusted for mother's age, ethnicity (Bedouin vs Jewish), parity, diabetes mellitus, lack of perinatal care, and the year of birth. Results: The study included 101 615 pregnancies, of which 6919 (6.8%) were exposed to amoxicillin: 1045 (1.0%) to amoxicillin only and 6041 (5.9%) to ACA. No significant association was found, in the univariate and multivariate analyses, between first‐trimester exposure to amoxicillin or ACA and major malformations in general (crude relative risk, 1.05 95% confidence interval 0.95–1.16; adjusted relative risk 1.09, 95% confidence interval 0.98–1.20), or for major malformations according to organ systems. No dose–response relationship was found between exposure in terms of the defined daily dose and major malformations. Conclusion: Exposure to amoxicillin and ACA during the first trimester of pregnancy was not associated with an increased risk of major congenital malformations.